A standardised biologging approach to infer parturition: An application in large herbivores across the hider‐follower continuum. Issue 6 (25th March 2021) - Marchand, Pascal; Garel, Mathieu; Morellet, Nicolas; Benoit, Laura; Chaval, Yannick; Itty, Christian; Petit, Elodie; Cargnelutti, Bruno; Hewison, Aidan J. M.; Loison, Anne
Abstract: The timing of birth has a predominant influence on both the reproductive success of the mother and the life‐history trajectory of her offspring. Because early growth and survival are key drivers of population dynamics, there is an urgent need to understand how global change is affecting reproductive phenology and performance. However, identifying when and where birth occurs is often difficult in the wild due to the cryptic behaviour of females around parturition, although this information may also help managers to protect reproductive females and newborn against human disturbance. While several approaches to identify parturition based on movement metrics derived from GPS monitoring have previously been proposed, their performance has not been evaluated over a range of species with contrasted movement characteristics. Here, we present a novel approach to detect parturition by combining data on animal movements, activity rate and habitat use. Using machine learning approaches, we evaluated the relative and combined performance of each category of metrics in predicting parturition for three large herbivores with contrasted life histories: a hider‐type species, the roe deer Capreolus capreolus and two follower‐type species, the Mediterranean mouflon Ovis gmelini musimon × Ovis sp. and the Alpine ibex Capra ibex . We first showed that detection of parturition was much improved when birth‐related modifications in the habitat use and activity rate of the mother were considered, rather than relying on movement metrics only. We then demonstrated that our approach was highly successful (76%–100% of events correctly identified) in detecting parturition in both follower and hider species. Furthermore, our approach generated estimates for peak birth date and the proportion of parturient females that were comparable with those based on direct observations at the population scale. Finally, our approach outperformed the most commonly employed methods in the literature which generally failed to identify non‐reproductive females for the three studied species, and provided birth timing estimates that only poorly match the true parturition date. We suggest that by combining sources of information, we have developed a standardised methodological approach for inferring parturition in the wild, not only for large herbivores but also for any species where parturition induces marked behavioural changes in the mother.